Analisis Pendidikan dan Moral terhadap Siswa Kurikulum Merdeka dengan Menciptakan Suasana yang Menyenangkan - Sri Yunita; Santiana Siboro (Public Service and Governance Journal, 2024)
Currently, education is facing various challenges due to significant changes in times. The extensive use of technology has influenced education to a large extent. Where education has an important role in answering and preparing the current and future generations. The Independent Curriculum is present as a solution to this problem, namely as a solution to give the right to learn independently. Through the impartial implementation of the P5 Curriculum, it is hoped that students will develop their talents more freely and creatively, even as people who are more objective and able to make brilliant contributions to society. This research method uses descriptive methods. This research aims to describe and analyze the educational management of the P5 program in the independent learning curriculum which will provide enjoyable learning. Efforts to strengthen the Pancasila student profile still need to be evaluated through teachers according to the needs and characteristics of each scholar. Therefore, teachers want to increase the potential for organizing and managing special memories so that they can be understood according to the wishes and interests of each student. Teachers need to have very good information about Pancasila values ​​and be able to integrate them into daily coaching. The conclusion of this article is that the independent learning program has brought many positive changes to the world of education in Indonesia. This article invites readers to understand more about the independent curriculum as a new curriculum and its advantages and benefits for educational units as well as for students.